2004
DOI: 10.1091/mbc.e03-08-0588
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Induces a Lateral Redistribution of α2β1 Integrin from Membrane Rafts to Caveolae and Subsequent Protein Kinase C-dependent Internalization

Abstract: Integrin ␣2␤1 mediates the binding of several epithelial and mesenchymal cell types to collagen. The composition of the surrounding plasma membrane, especially caveolin-1-and cholesterol-containing membrane structures called caveolae, may be important to integrin signaling. On cell surface ␣2␤1 integrin was located in the raft like membrane domain, rich in GPI-anchored proteins, rather than in caveolae. However, when antibodies were used to generate clusters of ␣2␤1 integrin, they started to move laterally on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
186
2
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(207 citation statements)
references
References 60 publications
18
186
2
1
Order By: Relevance
“…After a dynamin-dependent pinching process, the SV40-loaded caveolae leaves the plasma membrane and enters the caveosome before finally reaching the ER through microtubule-dependent transport. Polyoma virus and Echovirus 1 also enter cells through a similar pathway to SV40 (REFS [22][23][24] ).…”
Section: Viral Entrymentioning
confidence: 99%
“…After a dynamin-dependent pinching process, the SV40-loaded caveolae leaves the plasma membrane and enters the caveosome before finally reaching the ER through microtubule-dependent transport. Polyoma virus and Echovirus 1 also enter cells through a similar pathway to SV40 (REFS [22][23][24] ).…”
Section: Viral Entrymentioning
confidence: 99%
“…1 Prior studies suggest that caveolin-1 may associate with integrin and regulate integrin signaling. [25][26][27][28] Since we have found that during control fibroblast interaction with collagen, PTEN associates with caveolin-1 and suppresses activation of Akt, we were interested in determining whether ␤1 integrin also associates with caveolin-1 in a protein complex. We found that an endogenous protein complex consisting of caveolin-1, ␤1 integrin, and PTEN could be coprecipitated from normal fibroblasts ( Figure 5, A and B).…”
Section: A ␤1 Integrin/caveolin-1/pten Complex Is Present In Control mentioning
confidence: 99%
“…Clathrin-independent and caveolae-mediated internalization of integrins has been described for certain integrins including integrin ␣ 2 ␤ 1 . Caveolin-1 is associated with some integrins including ␣ v ␤ 3 and ␣ 5 ␤ 1 , and integrin ␣ 2 ␤ 1 redistributes to caveolae after integrin clustering (76). ␤ 1 integrins play an important role in the process of endocytosis of fibronectin and fibronectin matrix fibrils by caveolin-mediated event (75).…”
Section: Pharmacoproteomic Analysis Of P11mentioning
confidence: 99%